Investigating the Extent of Critical Thinking in Field-Dependent and Field-Independent Students’ Critical Thinking and Blogging - Zahra Shahsavar; Sefa Bulut (Vision: Journal for Language and Foreign Language Learning, 2022)
Identifying critical thinking and learners’ characteristics is very important in an online learning environment. This study investigated the extent of critical thinking between field-dependent and field-independent students’ critical thinking and blogging. It is a quasi-experimental in which a quantitative method was employed on an intact class of the students to develop their CT skills in their argumentative blog posts. Different aspects of CT skills, such as observation, inference, reasoning, assumption, and credibility were explained to the students. The GEFT developed by Witkin et al. (1971) was applied to evaluate the students' field dependency. Moreover, Newman et al. model (1996) was applied to analyze students’ CT in their blog posts.  No significant difference was found in the number of positive and negative CT indicators used by FD and FI students. Therefore, educators who wish to improve the students’ learning may train the students in CT skills by using a pre-planned and systematic procedure without worrying about learners’ cognitive styles, particularly their field dependency.